Sündige Menschen in der Gemeinschaft der Heiligen?: alte und neue Fragen nach der Kirchenzucht in ökumenischer Perspektive - Sattler, Dorothea (Zeitschrift für katholische Theologie, 2005)
The study deals with the theory of church discipline and practical experiences with it, with special reference to the decisions of the synod of the protestant church in the Rhineland. The discipline of the Eucharist is of special interest. Referring to the work of Lothar Lies the study concludes with a systematic reflection.